Conceptual Review: Compatibility of regulatory requirements of FSA to Insurance industry in Indonesia for Integrated GRC - Norimarna, Stefiany (RSF Conference Series: Business, Management and Social Sciences, 2021)
This study aims to obtain understanding and assurance whether the regulatory requirements of FSA for integrated GRC to the insurance industry are compatible with the requirements and suggested practices of ISO 37000 on Governance, ISO 31000 on risk management, and ISO 37301 on Compliance. The qualitative approach in which literature review and comparative study are conducted to find the degree of fitness of POJK with these ISO standards (ISO 37000, ISO 31000, and ISO 37301). This study found out that the regulatory requirements set forth by FSA (Financial Services Authority) to Insurance Industry for integrated GRC have all been compatible with all the elements of ISO 37000, ISO 31000, and ISO 37301. It means Insurance companies could use those ISO as standards. Therefore, it would be some efforts needed by the industry to carry out their learning curves in assuring the implementation of integrated GRC is continuously calibrated to their respective context either as an insurance company in general or as a particular organization that has its own respective and unique characteristic. The result of this paper could be used as generic inputs and considerations for insurance companies that have initiated their integrated GRC practices and/or just recently commenced and/or improved their practices more effectively.